Hyperreactio luteinalis: benign disorder masquerading as an ovarian malignancy - P., Kaur P.; ., Ashima; R., Isaacs; S., Goyal (International Journal of Research in Medical Sciences, 2018)
Hyperreactio luteinalis (HL) refers to pregnancy related moderate to marked enlargement of the ovaries due to multiple benign theca lutein cysts. It is caused due to elevated Human chorionic gonadotropins leading to maternal complications such as preeclampsia and preterm delivery may result. We report case of a 24 years old lady, G3P1A1L1 with spontaneous twin pregnancy at 13 weeks + 4 days gestation presented with chief complaint of lower abdominal pain on exertion for 5 days. Ultrasonography (USG) showed a large left ovarian mass in Pouch of Douglas pushing uterus up and extending into the left side of midline upto costal cartilage. It showed multiple thick septations with vascularity pointing towards malignancy. CA-125 was elevated to 193U/ml. Laparotomy was undertaken. Intraoperatively, bilateral huge, congested, bosselated, multicystic ovarian masses were present which replaced normal ovaries and appeared malignant. Bilateral oophorectomy was done. Specimens received for histopathological examination comprised of two large multilobulated, dark brown, ovarian masses with intact glistening capsule. Serial sections through both the masses showed thin walled, multiloculated cysts with smooth inner lining, filled with thin clear to hemorrhagic fluid. On microscopic examination diagnosis of Hyperreactio luteinalis, bilateral ovarian masses were made. HL can be misinterpreted on USG or laparotomy as ovarian malignancy resulting in unnecessary surgical intervention.